Physico-chemical and microbiological characterization of spontaneous fermentation of Cellina di Nardò and Leccino table olives - Bleve, Gianluca; Tufariello, Maria; Durante, Miriana; Perbellini, Ezio; Ramires, Francesca A.; Grieco, Francesco; Cappello, Maria S.; De Domenico, Stefania; Mita, Giovanni; Tasioula-Margari, Maria; Logrieco, Antonio F. (Frontiers in Microbiology, 2014)
Table olives are one of the most important traditional fermented vegetables in Europe and their world consumption is constantly increasing. In the Greek style, table olives are obtained by spontaneous fermentations, without any chemical debittering treatment. Evolution of sugars, organic acids, alcohols, mono and polyphenol compounds and volatile compounds associated with the fermentative metabolism of yeasts and bacteria throughout the natural fermentation process of the two Italian olive cultivars Cellina di Nardò and Leccino were determined. A protocol was developed and applied aimed at the technological characterization of LAB and yeast strains as possible candidate autochthonous starters for table olive fermentation from Cellina di Nardò and Leccino cultivars. The study of the main physic-chemical parameters and volatile compounds during fermentation helped to determine chemical descriptors that may be suitable for monitoring olive fermentation. In both the analyzed table olive cultivars, aldehydes proved to be closely related to the first stage of fermentation (30 days), while higher alcohols (2-methyl-1-propanol; 3-methyl-1-butanol), styrene, and o-cymene were associated with the middle stage of fermentation (90 days) and acetate esters with the final step of olive fermentation (180 days).